The Effect of Providing SKJ Gymnastics on The Physical Fitness of Grade Viii Students of SMP Negeri 2 Sitiung - Burhan, Maldin Ahmad; Prasetyo, Dian Estu; Sulistiani, Wafiq (The Future of Education Journal, 2024)
This research is motivated because in PJOK learning many students easily feel tired when the learning process takes place so that learning is not in accordance with the learning process and the lack of understanding of students about the importance of a fit and healthy body so that they follow the learning process just to follow. One of the things that can be done to overcome these problems is to provide SKJ exercises so that students do not feel tired in the learning process and can complete their tasks properly and can improve physical fitness in developing and increasing strength, endurance, speed, agility, flexibility, coordination, accuracy and balance. This study aims to determine how much influence the provision of SKJ gymnastics on physical fitness. This type of research is experimental research with Pre-experimental design I (Nondesigns), namely one gruop pretest-posttest. The population in this study were VIII grade students of SMP Negeri 2 Sitiung in the 2023/2024 academic year. The research sample used was class VIII students. Data collection techniques in this study were using TKJI tests and documentation, and the data analysis techniques used were normality tests, and t tests (hypotheses). The results showed that this SKJ exercise had an effect on students' physical fitness. Where the average value of the prettest is 16.13, while the average value of the posttest is 21.07, and the t test of the two data levels is significantly smaller than 0.05. The calculation results obtained sign < α (0.000 < 0.05). This shows that SKJ exercises have an effect on students' physical fitness.